Serum Cortisol Level as a Predictor of In-Hospital Mortality in Patients Undergoing Primary Percutaneous Intervention for ST Segment Elevation Myocardial Infarction - M Sudhakar Rao; Tom Devasia; Hashir Kareem; Padmakumar R; Ashwal AJ (Publisher: Shahid Beheshti University of Medical Sciences, 2019)
Introduction: Various laboratory markers have been proposed to assess prognosis in myocardial infarction. Serum cortisol is one such laboratory marker. There are only few studies done in the recent past which prove that cortisol is a prognostic marker in STEMI.Methods: We studied a total of 168 patients who presented with STEMI and underwent primary percutaneous intervention (PPCI) within 12 hours of symptom onset between April 2016 and November 2016.Results: The average age of study population was 61 ± 0.12 years. Males were predominant (n = 132, 78.57%). 155 patients survived, whereas 13 patients died in the hospital. Mean syntax score was 16.65 ±5. 33 among patients who died, whereas it was 13.11 ± 5.62 among survivors (P = 0.03). Mean cortisol was significantly higher among the patients who died (46.13 ± 14.61 mcg/dl) than the survivors (31.16 ± 13.16 mcg/dl) (P = 0.003). The ROC AUC for in-hospital mortality was 0.77 (95% confidence interval [CI], 0.645–0.897). An optimal cut-point identified from the ROC curve was a random serum cortisol concentration of 33.66 mcg/dl, with corresponding sensitivity and specificity of 69.2 % and 64 %, respectively. At a cut-point of 29.55 mcg/dl, sensitivity and specificity were 84.6 and 50 %, respectively.Conclusion: This study showed that serum cortisol level is a strong predictor of mortality in patients undergoing PPCI for STEMI. Levels more than 33.66 mcg/dl can predict mortality with a sensitivity of almost 70 percent and specificity of 64 percent.